The Effect of Nursing Students' Level of Readiness for Professional Practice on Self-Efficacy and Clinical Stress Perception: A Cross-sectional Study - Öner, Uğur; Yılmaz, Dilek; Aslan, Sinan; Çınar, Ercan (Makara Journal of Health Research, 2025)
Background: It is essential to evaluate students’ readiness before graduation and support them with education accordingly. This study investigates the effect of the level of readiness for professional practice as a purpose on the self-efficacy and clinical stress perceptions of nursing students. Methods: The data for this cross-sectional study were collected between May and July 2024. The study included 733 3rd and 4th-year students studying nursing departments at state universities in Turkey. The Student Identification Form, Casey-Fink Readiness for Practice Scale (CFRPS), Student Self-Efficacy Scale (SSS), and Nursing Students Perceptions of Clinical Stressors Scale (NSPCSS) were used. Results: The mean total CFRPS score of the students participating in the study was 43.85 ± 8.58, the mean SSS total score was 29.93 ± 5.84, and the mean NSPCSS total score was 95.36 ± 19.99. A statistically significant difference was found between the students' age, gender, class level, and willingness to choose the nursing department and the CFRPS, SSS, and NSPCSS scale scores (p < 0.05). The results indicated a negative correlation between the NSPCSS and both the CFRPS (r = −0.99, p = 0.01) and the SSS (r = −0.11, p = 0.01). Additionally, a strong positive correlation was observed between the CFRPS and SSS (r = 0.77, p = 0.01). Readiness explains 2.1% of the variance in self-efficacy and perception of clinical stress (R2 = 0.021, p = 0.001). Conclusion: As a result of this study, it was determined that nursing students’ readiness for professional practice, self-efficacy, and clinical stress perceptions were affected by various factors such as age, gender, grade level, and desire to choose the nursing department. In addition, it was concluded that there was a negative correlation between students' clinical stress perceptions and their readiness for professional practice and self-efficacy levels, and that as students' readiness and self-efficacy increased, their clinical stress perceptions tended to decrease.